Rancillac : Rétrospective 1962-2002. - Musée d'Art Moderne Saint-Etienne; Musée de l'Hospice Saint-Roch Issoudun; Musée des Beaux-arts Dole; Beauffet, Jacques; Wilson, Sarah (Dole Saint-Etienne Saint-Roch d'Issoudun : Musée d'Art Moderne de Saint-Etienne Métropole Musée de l'Hospice Saint-Roch d'Issoudun Musée des Beaux-arts de Dole, 2003)
The collections of the Musée des Beaux-Arts Dole, and the Musée d'Art Moderne Saint-Etienne, include major works by the French artist Bernard Rancillac, born in 1931. From March to December 2003 in collaboration with the Musée de l'Hospice Saint-Roch Issoudun these museums are holding a major retrospective on this significant figure in Narrative Figuration. In the economic and political context of the 1960s, Narrative Figuration marked the renewal of figurative art that was both critical and committed. Art became political, an instrument of communication rather than an object of contemplation, and legibility was the keyword. Consumerism was virulently attacked. From 1966 on Rancillac used photographs and images as the starting point for his work. He drew on his everyday life and current events to create tonic figurative paintings, with vivid colours and effective graphics. The monographic catalogue on Bernard Rancillac focuses on the pivotal series in which the artist's favourite themes are diffracted, comics, anger, jazz, the conventions of painting, mediatised images, sport, Algeria, women..
ind. tent., gr. tent., bibliog. p. 143-147
Frans
Exhibition. Rancillac : Rétrospective 1962-2002 (1). Exhibition. Rancillac : Rétrospective 1962-2002 (2). Exhibition. Rancillac : Rétrospective 1962-2002 (3). Musée d'Art Moderne de Saint-Etienne Métropole. Musée de l'Hospice Saint-Roch d'Issoudun. Musée des Beaux-arts de Dole. 2003-03-28. 2003-06-27. 2003-10-10. 2003-06-09. 2003-09-29. 2003-12-21
boek
Keywords: Rancillac, Bernard